Legal Consequences of an Authentic Deed Made by a Notary that is Partial and Dishonest According to Law no. 2 of 2014 concerning the Position of Notary - Muhammad Fadly Sembiring (Outline Publisher, 2025)
A notary is a public official who is authorized by the state to make authentic deeds. This position requires the implementation of duties honestly, carefully, independently, and impartially, because the deeds made become evidence for the parties and have high evidentiary power. In practice, deeds are still found that are drafted in a biased manner or contrary to the principle of honesty, thus giving rise to issues regarding the notary's obligations and the legal consequences arising from such deeds. This study aims to: describe the notary's obligations in making authentic deeds according to the provisions of laws and regulations and codes of ethics, and analyze the legal consequences of authentic deeds made in a biased and/or dishonest manner. The method used is normative legal research with a statutory, conceptual, and case approach. Primary legal materials include the Civil Code and the Notary Law and its amendments, accompanied by doctrine and court decisions as secondary materials. The analysis is carried out qualitatively - prescriptively. The research results show that a notary's obligations include verifying the identity and authority of the parties, reading the deed before the parties and witnesses, including the date/number and signature in accordance with official procedures, and maintaining independence. Violation of these obligations can result in formal and/or material defects in the deed. As a legal consequence, the deed can lose its authentic evidentiary force and only have value as a private deed, and can even be declared null and void, or become the basis for civil, administrative, ethical, and criminal liability as long as the elements are met. The research recommends strengthening procedural compliance, implementing the principle of prudence, and enhancing the effectiveness of oversight mechanisms for notaries.